Analyze the Language Used in Political News and Its Implications for Public Opinion: Analisis Bahasa yang Digunakan Dalam Berita Politik, Serta Implikasinya Terhadap Opini Publik - Fajrul Khaer; Ilmiawan; Aba, Akbar (Jurnal Riseta Soshum, 2025)
This research aims to analyze the role of language in political reporting and its impact on public opinion. Using the Critical Discourse Analysis (CDA) method, this research explores how the media uses language to frame political news, chooses diction with ideological connotations, and utilizes emotional language to influence public perception. Data was collected from political news published in several media with different political orientations, as well as through surveys and interviews with readers to identify the influence of language on their opinions. The research results show that the media, through framing techniques, word choice, and the use of language that contains emotional elements, significantly influences the public's perspective on political issues. This research also reveals the need to increase media literacy among the public so that the public is more critical in responding to political news and wiser in receiving information. It is hoped that these findings can contribute to understanding the influence of language in the media on the formation of public opinion, as well as inviting the media to be more responsible in delivering objective and informative news.